Evaluación de dosis de ácido húmico granulado de leonardita y ácidos húmicos y fulvicos con macro y micro nutrientes en el cultivo de cebollita china (Var. Roja chiclayana), bajo condiciones agroecológicas en la provincia de Lamas - Varas Abad, Pedro Luis (2012)
This paper titled "Evaluation of humic acid dose Leonardite granules and humic and fulvic acids with macro and micro nutrients in the cultivation of Chinese onion (red variety Chiclayo), agro-ecological conditions in the province of Lamas" had as objectives: To evaluate the effect of two doses of humic acid granular Leonardite, and two doses of humic and fulvic with macro and micro nutrients - liquid in the cultivation of Chinese onion (Allium fistolosum) (chiclayana red variety), and perform the analysis Economy of the treatments studied. The research was conducted on the farm "El Pacifico" located in the District of Lamas, Province of Lamas, San Martin Department. We used the statistical design of randomized complete block (RCBD) with four blocks, five treatments. The treatments were soil application of 300 and 400 kg / ha grain ac.húmicos (T1 and T2), the application every 15 days 50 to 80 Lt / ha of humic and fulvic with macro and micro elements (liquid) (T3 and T4) and a control (no application). The most relevant results were: The results of the evaluations stated that the treatments which was applied to humic and fulvic acids Leonardite with macro and micro elements - liquid (T3 and T4) showed higher mean values kg.ha1 performance, weight plant, mean diameter of the bulb, number of bulbs per plant and plant height compared to those treatments that were applied Leonardite granular humic acids (T1 and T2) and T3 treatment (Implementation of 50. Lt / ha humic acids, fulvic with macro and micro elements - liquid) had the highest rate of the Cost / Benefit to 1.05, which meant a return of 4.85%.